Modern directions of contemporary linguistics: functional context - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article is devoted to the analysis and differentiation of the concepts «modern linguistics» and «neolinguistics» in philology. It is stated that the defined notions are unclearly represented in modern science and require additional argumentation by the chronology and content of new ideas, concepts and theories. The thesis about special social, cognitive and civilizational status of the neolinguistic directions of knowledge, their prospects in a person’s intellectual activity is being argued. The author’s attention is focused on the integral nature of the modern directions of linguistics, which corresponds to the development tendencies of science and its social functions. The overview of separate structural subdivisions, specialties and specializations, tendencies of development of new directions of linguistic science in the leading universities of the world is offered. Information on the establishment of the medialinguistic commission of the International Committee of Slavists, an authoritative international organization of modern researchers in the humanities, is provided. It is postulated that the idea of changing the structural-functional paradigm of the 20th century on the cognitive-communicative paradigm of the 21st century requires additional argumentation.